Bringing them together: integrating economic and social-ecological dimensions in corporate decision-making - Mayers, Nadine (Research of GSB, 2017)
The integration of economic, social and environmental dimensions is essential for corporate sustainability. Integration requires that there be no a priori priority among these dimensions. Economic priorities, however, often dominate decision-making processes in for-profit organisations. This thesis asks how do organisations integrate predominant economic dimensions, on the one hand, and social-ecological dimensions, on the other? The question is focused on the middle management level, where relatively little is known about how competing organisational aspects are integrated. The study addresses a gap in theory relating to tensions in corporate sustainability by drawing on paradox, organisational ambidexterity and organisational identity literatures. The case study explored the research question from the lived experience of purposefully sampled research participants in a century-old mining company. The study focused on the integration of economic and social-ecological (E&SE) dimensions in the cross-functional decision-making process where mining projects are developed. Findings from the inductive analysis before and after the introduction of an intentional integration process revealed five dimensions of differentiation that were further explored. The analysis culminated in a process model of E&SE integration. I argue that E&SE integration on the middle management level is characterised by tensions between competing, interrelated priorities that constrain integration. Notwithstanding organisational commitment to corporate sustainability and E&SE integration, failure to manage these tensions perpetuates unsustainable outcomes in decision-making processes. The overarching contribution to corporate sustainability literature is a process model of E&SE integration on the middle management level that addresses the tensions that constrain integration. Integration is enabled by suspending premature convergence on a single option and by bringing social-ecological dimensions to the forefront in order to explore how E&SE dimensions are interdependent, before making binding choices. The study contributes to organisational ambidexterity literature by showing how the integration of strategic priorities on the middle management level is distinct from integration on the senior management level with respect to the quality of the decision and the locus of integration. The study also contributes to an emerging scholarly conversation regarding organisational purpose by identifying how reframing purpose into an integrative metaframe can enable commitment to an integrated decision-making process.